Molecular Characterization of Wild and Cultivated Strawberry (Fragaria × ananassa) through DNA Barcode Markers. (11th October 2022) - Qarni, Awais; Muhammad, Khushi; Wahab, Abdul; Ali, Amir; Khizar, Chandni; Ullah, Izhar; Kazmi, Abeer; Sultana, Tahira; Hameed, Asma; Younas, Muhammad; Rahimi, Mehdi
Abstract : Background . DNA barcoding is a useful technique for the identification, conservation, and diversity estimation at the species level in plants. The current research work was carried out to characterize selected Fragaria species from northern Pakistan using DNA barcode markers. Methodology . Initially, the efficacy of eight DNA barcode markers was analyzed based on the amplification and sequencing of the genome of selected Fragaria species. The resultant sequences were analyzed using BLAST, MEGA 7.0, and Bio Edit software. The phylogenetic tree was constructed by using Fragaria current species sequences and reference sequences through the neighbor-joining method or maximum likelihood method. Results . Among eight DNA barcode markers, only two ( ITS2 and rbclC ) were amplified, and sequences were obtained. ITS2 sequence was BLAST in NCBI for related reference species which ranged from 89.79% to 90.05% along with Fragaria vesca (AF163517.1) which have 99.05% identity. Similarly, the rbclC sequence of Fragaria species was ranged from 96% to 99.58% along with Fragaria × ananassa (KY358226.1) which had 99.58% identity. Conclusion . It is recommended that DNA barcode markers are a useful tool to identify the genetic diversity of a species. Moreover, this study could be helpful for the identification of the Fragaria species cultivated in other regions of the world.